14v+v-11v+3v-7=7

Simple and best practice solution for 14v+v-11v+3v-7=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14v+v-11v+3v-7=7 equation:


Simplifying
14v + v + -11v + 3v + -7 = 7

Reorder the terms:
-7 + 14v + v + -11v + 3v = 7

Combine like terms: 14v + v = 15v
-7 + 15v + -11v + 3v = 7

Combine like terms: 15v + -11v = 4v
-7 + 4v + 3v = 7

Combine like terms: 4v + 3v = 7v
-7 + 7v = 7

Solving
-7 + 7v = 7

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 7v = 7 + 7

Combine like terms: -7 + 7 = 0
0 + 7v = 7 + 7
7v = 7 + 7

Combine like terms: 7 + 7 = 14
7v = 14

Divide each side by '7'.
v = 2

Simplifying
v = 2

See similar equations:

| 6x+2/3=-5/24 | | 3y-y=10 | | 1/7x-1/8x=3 | | 7u-5u-u-1=17 | | 2a+12=15 | | 12X^2-180x+464=0 | | h=-5t^2+30 | | t+w=12 | | 12w-12w+4w-3w-1=6 | | -5-6+(-1)-(-7)= | | -2z-16z-12z-9z-8z=20 | | 4h+2h-5h+3=13 | | x^3+x=2 | | Y=-3+6x | | -8-(-2)-(-1)= | | 25-3x=19 | | 10n+-3n-19=-16 | | 2x^3+6x^2+6x-7=0 | | -5x+2=62 | | -d-14d-12d=-10 | | 2x+62=5 | | 4g+6g+8g+-9g-8=20 | | 19-5/2*x=34 | | -12*x-17=-89 | | 8-1/3*x=16 | | 4a+6b=ab | | -8x-48x+49x+9x-10x-48=-24 | | -9+-5= | | 8y-6y-y+y-y=14 | | -17s+16s+13s-18s=12 | | 12X^2-156x+350=0 | | 3x+8=-28 |

Equations solver categories